SYNTHESIS OF SINGLE-PHASE HYDROXYAPATITE POWDER FROM EGGSHELL WASTE VIA CO-PRECIPITATION METHOD AND ITS STRUCTURAL CHARACTERIZATION - Musyarofah, Musyarofah; Mahera, Adinda Kholif; Tajalla, Gusti Umindya Nur; Nafisah, Azmia Rizka; Prayitno, Budi; Norhidayah, Siti; Kartika, Siska Ayu (Indonesian Physical Review, 2025)
This study aims to synthesize a single-phase hydroxyapatite powder using waste chicken eggshells as a calcium source via the co-precipitation method. The process focuses on optimizing calcination time and temperature to achieve high-purity hydroxyapatite.  The co-precipitation procedure involved controlled pH adjustment and aging time, contributing to the formation of homogeneous particles. Chicken eggshells, predominantly composed of calcium carbonate (CaCO3), were calcined at 1000°C for 15 hours to produce calcium oxide (CaO). The resulting CaO was then reacted with phosphate ions in an aqueous solution, followed by a calcination at 900°C for varying holding times of 5 and 10 hours. X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and Brunauer-Emmett-Teller (BET) analysis were conducted to evaluate phase composition, crystal size, and texture properties. The optimum condition was found at 900 °C for 10 h calcination, resulting in single-phase hydroxyapatite, a crystallite size of 220 nm, an average pore radius of 6.78 nm, a total pore volume of 0.02 cc/g, a surface area of 6.38 m2/g, and an average particle radius of 213.89 nm. These findings highlight the potential of this method for producing bioceramics with desirable properties for use in bone grafts and other biomedical materials.